2022
DOI: 10.1101/2022.04.26.22274275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prostate cancer androgen receptor activity dictates efficacy of Bipolar Androgen Therapy

Abstract: Testosterone is the canonical growth factor of prostate cancer but can paradoxically suppress its growth when present at supraphysiological levels. We have previously demonstrated that the cyclical administration of supraphysiological androgen (SPA), entitled Bipolar Androgen Therapy (BAT), can result in tumor regression and clinical benefit for patients with castration-resistant prostate cancer [1–5]. However, predictors and mechanisms of response and resistance have been ill-defined. Here we show that growth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(76 reference statements)
1
1
0
Order By: Relevance
“…Aggregating cancer clusters 1-8 and performing differential expression and pathway analysis of this aggregated cancer cluster against benign luminal cell clusters revealed that the Hallmark MYC Targets V1 gene set was the top upregulated pathway and androgen response the top downregulated pathway in the cancer clusters (Figure 2G, and Table S4). The universal upregulation of MYC targets and downregulation of the androgen response pathway across all cancer clusters are consistent with recent reports characterizing the antagonistic relationship between MYC and androgen response genes [51][52][53] . Including the Dang MYC Targets Up gene set in GSEA 54 reaffirmed significant upregulation of MYC targets across all cancer clusters (Figures 2F-G).…”
Section: Myc Activation Is a Common Denominator Across The Known Mole...supporting
confidence: 90%
“…Aggregating cancer clusters 1-8 and performing differential expression and pathway analysis of this aggregated cancer cluster against benign luminal cell clusters revealed that the Hallmark MYC Targets V1 gene set was the top upregulated pathway and androgen response the top downregulated pathway in the cancer clusters (Figure 2G, and Table S4). The universal upregulation of MYC targets and downregulation of the androgen response pathway across all cancer clusters are consistent with recent reports characterizing the antagonistic relationship between MYC and androgen response genes [51][52][53] . Including the Dang MYC Targets Up gene set in GSEA 54 reaffirmed significant upregulation of MYC targets across all cancer clusters (Figures 2F-G).…”
Section: Myc Activation Is a Common Denominator Across The Known Mole...supporting
confidence: 90%
“…Clinical investigations have shown that BAT is effective ( 12 14 ). Thus, BAT is safer and more effective than cytotoxic drugs ( 15 ). BAT can restore some patients’ sensitivity to drugs, such as Abi and Enz, showing significant advantages in treating CRPC patients ( 16 ).…”
Section: Introductionmentioning
confidence: 99%